Stability of liquid smoked nano-encapsulated on the foodborne pathogens and histamine-forming bacteria’s growth in tuna loin sashimi. - DIEN, Henny Adeleida; MONTOLALU, Roike Iwan; Mentang, Feny; BERHIMPON, Siegfried (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: In Japan, sashimi, a distinctive and straightforward meal of fresh fish, is frequently offered for dinner with family or at restaurants. Since sashimi is made from raw tuna loin, infections and spoiling microorganisms can readily damage it, especially if it is served without refrigeration. In addition to ice, novel preservatives need to be researched to prevent the growth of harmful and histamine-producing microbes. Carbonyl, phenols from burning coconut shells, and organic acids are among the antibacterial substances found in liquid smoke (LS). However, more study on liquid smoke nano-encapsulation is needed because there is a lack of evidence about the physicochemical properties of LS. The goal of the study was to determine the production process of liquid smoke nano-encapsulation (LSN), the level of total histamine in LSN-coated sashimi stored at room temperature, and the effectiveness of LSN against pathogenic microorganisms. METHODS: The following parameters were measured: pH levels, water content, Salmonella, E. coli, total microbial count (TPC), histamine concentration, and antibacterial inhibitory action. RESULTS: The findings demonstrated that LSN with maltodextrin: sago flour: 1% LS ratio of 10: 1: 5 effectively inhibited the growth of E. coli and Salmonella and decreased the amount of histamine in sashimi that was refrigerated for ten days.